Incidence and Risk Factors of White Matter Lesions in Moderate and Late Preterm Infants - Kentaro Ueda; Kennosuke Tsuda; Takaharu Yamada; Shin Kato; Sachiko Iwata; Shinji Saitoh; Osuke Iwata (Diagnostics)
Background: Moderate and late preterm infants (32–36 weeks of gestation) are at significant risk of developmental impairments. Incidence of white matter lesions, which are associated with developmental impairments in very preterm infants, remains underreported in this population. This study aimed to assess the incidence and clinical risk factors associated with brain lesions, particularly white matter lesions, in moderate and late preterm infants using term-equivalent MRI. Methods: This prospective observational study included 195 preterm infants born at 32+0–36+6 weeks of gestation and admitted to a tertiary NICU between 2019 and 2020. MRI findings at term-equivalent age were evaluated. Clinical risk factors were analysed using logistic regression. Results: Among the 195 infants, 23.6% had brain lesions on MRI, with white matter lesions (73.9%), specifically punctate white matter lesions, being the most common form of lesions. Vaginal delivery (odds ratio (OR) = 3.102, 95% confidence interval (CI) = 1.250–7.696, p = 0.015), larger birth weight z-scores (OR = 1.702, 95% CI = 1.118–2.591, p = 0.013), and intubation (OR = 2.948, 95% CI = 1.269–6.850, p = 0.012) were significant risk factors for white matter lesions. Conclusions: White matter lesions, particularly punctate white matter lesions, are common in moderate and late preterm infants. These lesions are associated with perinatal factors suggestive of delayed transition and inflammation. Future research should focus on detailed clinical care measures and neurodevelopmental assessments to identify modifiable risk factors for brain injury.